Recurrent vulvovaginitis: a psychosomatic disease? - Cordeiro, Sílvia N.; Giraldo, Paulo C.; Sabatino, José Hugo; Fonsechi-Carvasan, Gislaine A.; Turato, Egberto R. (Brazilian Journal of Sexually Transmitted Diseases, 2004)
Introduction:Episodes of vulvovaginitis are quite definitely one of the most common gynecological complaints that lead women to consult a gynecologist.The reasons for frequent recurrences have not been clearly established. Objectives:identify psychological aspects related to recurrent vulvovaginitis.Methods: Fifty-one women presenting a microbiological diagnosis of recurrent vulvovaginitis and 61 women with no complaint were studied. This studywas carried out at the department of Gynecology, the State University of Campinas (Unicamp, SP. Brazil) June 2001 to July, 2002. After informed consent,all the patients were submitted to a structured interview to investigate the psychological aspects, which allowed an in-depth aspect in the questions relatedto their emotional life and concerning to development theirself sexuality. The association between the psychological aspects and the study groups was car-ried out basead on the Multiple Correspondence Analysis. Results: The statistical analyses dates were done using Multiple Correspondence model, thatpoint out psychological aspects the women presenting recurrent vulvovaginitis related to personal relationship with your parents and your sexual experien-ces before and after to menarc. A whole set of internal characteristics was associated to women presenting recurrent vulvovaginitis. Also, the study groupwomen showed to have negative impression of the relationship between their own parents. Conclusion: The recurrent vulvovaginitis seem to be a psycho-somatic of disease expression, possibly associated to conflicts related to marital strife between the patients’parents, and the patients’difficulties in relatingto maternal figure.